Design of Real-Time Aquarium Monitoring System for Endemic Fish on the Smartphone - Naufal Inas Fikri; Vito Louis Nathaniel; Muchamad Syahrul Gunawan; Tomy Abuzairi (Universitas Ahmad Dahlan, 2021)
The high rate of decreasing population of endemic fish species is becoming more severe over time. Therefore, it needed an effort to bring back the stability of the number. One of the reasons for the decreasing population is the changing environment due to climate change and the difficulty of treatment for this species. This research aims to design an aquarium monitoring system for endemic fish. The main components for this system are microcontroller ESP32 DOIT, Temperature Sensors DS18B20, DF Robot Analog pH Sensors, ESP32 Cam, UV Lamp, and Blynk server. The experiment was conducted by monitoring the aquarium environment using sensors and comparing it with the reference sensors. With a monitoring system, we can find out whether the current condition of the aquarium is in accordance with the fish's living environment or not. The monitoring results show that the average error for temperature is 0.14% and for pH is 0.67%. These results indicate that the prototype sensors are linear with reference sensors. Besides that, a real-time monitoring system is easy to use and more attractive because of smartphone utilization to monitor fish with a camera and lamp.